Pengaruh Gaya Kepemimpinan Model Ohio dan Beban Kerja Terhadap Kinerja Karyawan Pada Kantor PT Bio Farma (Persero) Kota Bandung - Simbolon, Angelita Mutiara; Syarifuddin (Fakultas Ilmu Administrasi Universitas Dr. Soetomo, 2025)
The Ohio Model Leadership Style is a study that aims to consider a leader's actions and identify the extent to which a certain leadership style has an impact on group performance and satisfaction. There are several indicators that affect employee performance, including leadership style and workload. This study aims to find out how the Ohio Model leadership style and workload affect employee performance at the PT Bio Farma (Persero) Bandung City office. In this study, the author used descriptive method analysis and quantitative method. The study took samples from 95 employees, in determining the sampling technique using the sample probability technique using the Slovin formula. The analysis method uses the Partial Least Square-Structural Equation Model (PLSSEM). The results of the description study showed that Ohio Model's leadership style, workload, and employee performance were in the good category. Partially, the Ohio Model leadership style has a positive and significant effect on employee performance and workload has a positive and significant effect on employee performance. The Ohio Model leadership style and workload have a positive and significant effect simultaneously on employee performance at PT Bio Farma (Persero) Bandung City